Evaluation of seed yield and oil contents in four materials of ricinus communis l. (2011)
Four castor materials were evaluated in 2009 in the middle region of Valle del Sinu, Colombia. The variables were phonological development, plant height, seed production and oil yield, in order to determine the best material for commercial purposes. All materials reported high yields of oil seeds and highlighting the commercial genotype Nordestina BRS149, 2.2 t ha-1 seed and 47% oil content. Planting distances were 1.5 x 1.5 m and 2.0 x 2.0 m, with densities of 6,666 and 3,906 plants ha-1, respectively. The plant height, seed productivity and oil yield showed significant differences for the interaction density × material; while comparing each material density, seed production only showed differences. These variables were significantly different between population densities, which shows that the higher the plant height, lower productivity. The planting distance of 2.0 x 2.0 m, provides higher productivity per plant values but seed oil yields were not different between densities. The oil quality parameters were assessed using free fatty acid value, iodine, acidity index, saponification, refraction and specific gravity, found that planting distance does not affect the quality of oil.